2016
DOI: 10.7812/tpp/15-060
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Type of Original Psoriasis Publications by Decade, 1960 to 2010

Abstract: Context:Research investigating psoriasis has spanned decades, and as our understanding of the disease has evolved, the focus of publications has changed.Objective: We sought to characterize the trends in original psoriasis-related research from 1960 to 2010 chronologically by decade.Methods: A literature review was performed using the keyword psoriasis in the MED-LINE database. All original psoriasis-related articles published at the beginning of each decade were searched and categorized by study type and topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The difficulty of Arab countries in catching up with psoriasis research can be related to the trends being oriented towards genetics and biologic therapy in psoriasis; publications in immunology and pathogenesis of psoriasis grew quickly between 1960 and 1990 with a rise of 488% and then continued to grow steadily with a growth of 66% more articles in 2010 as compared to 1990 20 . Immunological and genetic studies are conducted in advanced laboratories and need significant financial support, whereas in Arab countries, only 0.15% of the GDP is spent on research and development, which is well below the world average of 1.4% 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty of Arab countries in catching up with psoriasis research can be related to the trends being oriented towards genetics and biologic therapy in psoriasis; publications in immunology and pathogenesis of psoriasis grew quickly between 1960 and 1990 with a rise of 488% and then continued to grow steadily with a growth of 66% more articles in 2010 as compared to 1990 20 . Immunological and genetic studies are conducted in advanced laboratories and need significant financial support, whereas in Arab countries, only 0.15% of the GDP is spent on research and development, which is well below the world average of 1.4% 21 .…”
Section: Discussionmentioning
confidence: 99%
“…5 Following cyclosporine's observed clinical benefit in the 1970s, basic science publications on psoriasis immunopathogenesis exploded. 6,7 Further, a dramatic shift in literature from phototherapy to biologics occurred following anti-TNF medication's observed efficacy, laying the foundation for psoriasis' current understanding of pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that bibliometric analyzes of psoriasis articles from different periods concluded that biologic treatments were the focus of research. This can be attributed to the dual critical roles that T cells play in psoriasis, serving as both contributors to the disease's pathogenesis and potential targets for therapeutic intervention [ [12] , [13] , [14] ]. Herein, a bibliometric analysis was conducted to assess research on T cells in psoriasis; we systematically analyzed research content, development trends, and noteworthy achievements regarding T cells in psoriasis over the past 20 years and identified potential directions for future research.…”
Section: Introductionmentioning
confidence: 99%